DEXMEDETOMIDINE PROVIDES BETTER HEMODYNAMIC STABILITY COMPARED TO CLONIDINE IN SPINE SURGERY - Suyasa, I Ketut; Ryalino, Christopher; Pradnyani, Ni Putu Novita (Bali Journal of Anesthesiology, 2018)
Introduction: Spine surgery presents a number of challenges to the anesthesiologist. The Î±2 adrenergic agonist drugs are commonly used in such cases to provide hemodynamic and sympathoadrenal stability. Dexmedetomidine (DEX) is one of the most potent and highly selective Î±2-adrenergic receptor agonists. Another Î±2 adrenergic agonist drug that is used widely is clonidine. The study aims to compare both drugs in terms of hemodynamic stability in spine surgeries.Patients and Methods: 30 patients underwent spinal surgery were classified into one of the following group: DEX group (received DEX 1 mcg/kg in 10 minutes followed by 0.5 mcg/kg/hour during the course of the surgery) or CLO group (received clonidine 1 mcg/kg in 10 minutes followed by 1 mcg/kg/hour during surgery), by consecutive sampling. All other treatments and medications were similar in both groups. The systolic and diastolic blood pressure, mean arterial pressure, and heart rate were recorded every 5 minutes. Data was then analyzed by SPSS.Result: The patients in the DEX group had a better mean arterial pressure (p=0.002) and heart rate (p=0.018) stability compared to those in the CLO group.Conclusion: The administration of dexmedetomidine provides a better hemodynamic stability compared to clonidine in patients underwent spinal surgery.